2020
DOI: 10.1055/a-1293-9867
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Relative Configuration of Propargyl Cyclopropanes by Co-Crystallization

Abstract: Determining the diastereoselectivity of new synthetic molecules can be a challenge when NMR methods fail and the compounds are difficult to crystallize. Encapsulating organic crystals (EnOCs) can be used to overcome this challenge. Here we show that the diastereomeric configuration of racemic mixtures of propargyl cyclopropanes can be determined by co-crystallization with 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro) and X-ray crystallography. Three crystal structures are reported that unambigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Some tetraaryladamantane ethers have attracted inte­rest because of their ability to include other molecules in their crystalline lattice. 24 25 26 27 28 29 30 31 32 Building on earlier work on diaryladamantanes 17 we recently showed that 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyadamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro) are able to act as crystalline hosts for liquid compounds. This property makes them useful as crystalline coats for hazardous or reactive compounds, 30 or reversible uptake of volatile organic compounds from the gas phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some tetraaryladamantane ethers have attracted inte­rest because of their ability to include other molecules in their crystalline lattice. 24 25 26 27 28 29 30 31 32 Building on earlier work on diaryladamantanes 17 we recently showed that 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyadamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro) are able to act as crystalline hosts for liquid compounds. This property makes them useful as crystalline coats for hazardous or reactive compounds, 30 or reversible uptake of volatile organic compounds from the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most interesting crystallization chaperone, co-crystallizing with analytes up to a molecular weight of 242 g/mol, is TBro. 28 Unfortunately, TBro is accessible in modest yields only, not exceeding 20% for the Friedel–Crafts alkylation step starting from TOA and bromoanisole. Unlike the aryl starting materials for TDA and TEO, bromoanisole 3 contains two different substituents on its phenyl ring, either of which is ortho / para -directing, so that regioisomers are likely to be formed in the alkylation step.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Lastly, we have recently reported tetraaryladamantanes (TAAs) that can encapsulate liquid organic and inorganic compounds in their crystal lattices. [15][16][17][18][19][20] Three tetraaryladamantane ethers have been shown to readily crystallize as solvates when a hot solution in the liquid of interest is allowed to cool to room temperature. Encapsulation has been observed for a broad range of organic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…[17] A third TAA with an unusually high propensity to crystallize as solvate from solutions of different liquids is 1,3,5,7-tetrakis(2bromo-4-methoxyphenyl)adamantane (TBro), which was identified in our study on the determination of the absolute configuration of chiral analytes upon encapsulation. [18] In many cases, at least one guest molecule was found to be well ordered when encapsulated in TDA, TEO or TBro, so that the relative [19] or absolute stereochemistry can be revealed, qualifying the TAAs as a crystallization chaperone. [18] Still, for all TAA chaperones identified thus far, there is also a solvate-free form with similar crystallographic density as the solvates.…”
Section: Introductionmentioning
confidence: 99%
“…Three tetraaryladamantanes (TAAs) were found to show this behavior as hosts, namely 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyphenyl)adamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro). The X-ray crystal structures of over 100 EnOCs have been reported thus far [13][14][15][16], including structures with chiral guests that allow for the determination of the absolute [17] or relative configuration [18]. One limitation of the EnOC method was that the guest compound to be encapsulated had to be a liquid, so that it could act as solvent for the TAA, which would rapidly crystallize upon cooling of a hot, saturated solution.…”
Section: Introductionmentioning
confidence: 99%